Examining the relationship between psychological distress and adherence to anti-retroviral therapy among Ugandan adolescents living with HIV. Issue 7 (2nd July 2016) - Mutumba, Massy; Musiime, Victor; Lepkwoski, James M.; Harper, Gary W.; Snow, Rachel C.; Resnicow, Ken; Bauermeister, Jose A.
ABSTRACT: Psychological distress is common among adolescents living with HIV (ALHIV) worldwide, and has been associated with non-adherence to anti-retroviral therapy (ART), leading to poor virologic suppression, drug resistance, and increased risk for AIDS morbidity and mortality. However, only a few studies have explored the relationship between psychological distress and ART adherence among adolescents in sub-Saharan Africa. The paper examines the relationship between psychological distress and ART adherence, and effect of psychosocial resources on ART adherence. We conducted a cross-sectional survey of 464 ALHIV (aged 12–19; 53% female) seeking HIV care at a large HIV treatment center in Kampala, Uganda. ALHIV were recruited during routine clinic visits. Three self-reported binary adherence measures were utilized: missed pills in the past three days, non-adherence to the prescribed medical regimen, and self-rated adherence assessed using a visual analog scale. Psychological distress was measured as a continuous variable, and computed as the mean score on a locally developed and validated 25-item symptom checklist for Ugandan ALHIV. Psychosocial resources included spirituality, religiosity, optimism, social support, and coping strategies. After adjusting for respondents' socio-demographic characteristics and psychosocial resources, a unit increase in psychological distress was associated with increased odds of missing pills in past 3 days (Odds Ratio(OR) = 1.75; Confidence Interval (CI): 1.04–2.95), not following the prescribed regimen (OR = 1.63; CI: 1.08–2.46), and lower self-rated adherence (OR = 1.79; CI: 1.19–2.69). Psychosocial resources were associated with lower odds for non-adherence on all three self-report measures. There is a need to strengthen the psychosocial aspects of adolescent HIV care by developing interventions to identify and prevent psychological distress among Ugandan ALHIV.